IMPROVING THE SYSTEM OF TEACHING ENGLISH IN NOPHYLOLOGICAL EDUCATION - Bakhtiyarovna, Raximova Shahlo (International Journal of Psychosocial Rehabilitation, 2020)
This article describes some methodological issues of modernization of the English language teaching system in the field of non-philological education. The author identifies the criteria and indicators for assessing the effectiveness of English language teaching in students of non-philological education. He also developed recommendations for the use of methodological methods and tools for organizing and diagnosing the process of teaching students to create a communication text.